Barley Ant1 is a homolog of maize C1 and its product is part of the regulatory machinery governing anthocyanin synthesis in the leaf sheath. Issue 4 (10th June 2015) - Shoeva, Olesya Y.; Kukoeva, Tatyana V.; Börner, Andreas; Khlestkina, Elena K.; Saranga, Y.
Abstract Anthocyanins contribute to plants' defence against a number of abiotic and biotic stress agents. The anthocyanin pigmentation of the barley leaf sheath is genetically determined by Ant1, a gene which maps to a region of chromosome 7HS delimited by the microsatellite loci Xgbms0226 and Xgbms0240. The sequence of the maize gene C1 (encoding an R2R3 MYB factor regulating anthocyanin synthesis) was used for the PCR‐based cloning of Ant1. In ant1 genotypes, no transcript is generated in the leaf sheath, whereas the gene is active in the presence of the dominant allele. A comparison of the coding and promoter sequences of Ant1 (which induces purple pigmentation in the leaf sheath) and ant1 (which does not) showed that the key polymorphisms lay in the promoter sequence. The transcription of four anthocyanin synthesis structural genes (Chi, F3h, Dfr, Ans) was dependent on the allelic status of Ant1.